Identifying the Core Professional and Interpersonal Competencies: Findings from Competency-Based Approach - Zhumaliyeva, Rakhima; Kozhakhmet, Kanat; Atymtayeva, Lyazzat; Muratkyzy, Akbota (The Journal of Educational Development, 2020)
The issues of improving the university and postgraduate training of specialists in the Republic of Kazakhstan based on a competence approach have become an obvious factor of globalization on education system and development. According to the evolution of the competence education development, there are three basic approaches in assessing the quality of learning outcomes based on the concept of competencies: the behavioral approach (that is used in the US); functional approach (considered in the UK); multidimensional and holistic approaches (taken in France and Germany).This research is carried out within the framework of the Ministry of Education and Science of Republic of Kazakhstan grant project Ã¢â‚¬Å“Developing and implementing the innovative competency-based model of multilingual IT specialist in the course of national education system modernizationÃ¢â‚¬Â. The main objective of this study is to determine the competencies that are necessary for a modern IT specialist. The authors provide an analysis of core professional and interpersonal competencies. The results of this research will give effective opportunities for the meaningful conceptualization of educational programs and curricula for training modern IT specialists who will be in demand at the labour market.